In-Vivo Measurement of Ocular Deformation in Response to Ambient Pressure Modulation - Kling, Sabine (Frontiers in Bioengineering and Biotechnology, 2021)
A novel approach is presented for the non-invasive quantification of axial displacement and strain in corneal and anterior crystalline lens tissue in response to a homogenous ambient pressure change. A spectral domain optical coherence tomography (OCT) system was combined with a custom-built set of swimming goggles and a pressure control unit to acquire repetitive cross-sectional scans of the anterior ocular segment before, during and after ambient pressure modulation. The potential of the technique is demonstrated in vivo in a healthy human subject. The quantification of the dynamic deformation response, consisting of axial displacement and strain, demonstrated an initial retraction of the eye globe (-0.43 to -1.22 nm) and a subsequent forward motion (1.99 nm) in response to the pressure change, which went along with a compressive strain induced in the anterior crystalline lens (-0.009) and a tensile strain induced in the cornea (0.014). These mechanical responses appear to be the result of a combination of whole eye motion and eye globe expansion. The latter simulates a close-to-physiologic variation of the intraocular pressure and makes the detected mechanical responses potentially relevant for clinical follow-up and pre-surgical screening. The presented measurements are a proof-of-concept that non-contact low-amplitude ambient pressure modulation induces tissue displacement and strain that is detectable in vivo with OCT. To take full advantage of the high spatial resolution this imaging technique could offer, further software and hardware optimization will be necessary to overcome the current limitation of involuntary eye motions.